Edward Malefakis (1932-2016) y sus semillas: España, la Europa del Sur y la historia agraria en perspectiva global - Bonnet, Romain (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2018)
This article provides empirical evidence of how and why agrarian history, from the local to the global, can fruitfully inspire new perspectives on the outstanding research of the the American historian and hispanist Edward Malefakis (1932–2016). The first two parts are based on his work on Spain and Europe and open an epistemological discussion. The third part offers a careful analysis, involving a large array of original sources, of a case emphasised in Edward Malefakis’s masterpiece on the Spanish Second Republic (1931–1936) and its “rural oligarchy”. Political violence is highlighted as a massive phenomenon in the predominantly rural world, situated in its European and global dimensions. In order to articulate the local and broader levels, this article establishes a dialogue between the quantitative and qualitative approaches mobilized in this empirical overview, and thereby introduces an innovative use of the heuristic category and epistemological tool of the “exceptional normal”.
Keywords: Edward Malefakis; Agrarian History; Spanish Second Republic; Violence; Exceptional Normal